Dimensi k-Metrik Pada Graf Parasut Diperumum - Rahmadi, Deddy; Susanti, Yeni (Program Studi Matematika, Universitas Nusa Cendana, 2024)
Given a simple and connected graph G=(V(G), E(G)) and positive integer k. Set S V(G) is k-metric generator if for every pairs of distinct vertices u,v V(G), there exists at least k vertices w_1, w_2, …, w_k S such that d(u,w_i) ≠ d(v,w_i) for every i {1,2,…, k}, with d(u,v) is length of shortest path form u ke v. The k-metric generator with minimum cardinality is called k-metric bases, and the cardinalty is k-metric dimension of Gdenoted by dim_k(G). This research will discuss the k-metric dimension of generalized parachute graphs.